A Novel Microendoscopically Assisted Approach for the Treatment of Recurrent Lumbar Disc Herniation: Transosseous Discectomy Surgery - Nomura, Kazunori; Yoshida, Munehito; Kawai, Masaki; Okada, Motohiro; Nakao, Shin-ichi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background and Object Microendoscopic discectomy (MED) is still regarded as contraindicated for the treatment of recurrent lumbar disc herniation by many surgeons. Moreover, the presence of epidural scar tissue makes surgical manipulation difficult. To successfully remove the herniated disc in such cases, an open technique with a wide exposure may be required. We devised a new minimally invasive endoscopic approach, which is using a transosseous route. This is a retrospective review of a consecutive case series to examine the operative and clinical results of this new approach.Material and Methods Fifty-seven patients who underwent surgery for recurrent lumbar disc herniation were divided into two groups based on the operative procedure. Thirty patients underwent microendoscopic transosseous discectomy (TD) and 27 underwent MED. We graded operative results and clinical outcomes using the Japanese Orthopaedic Association (JOA) score for low-back pain before surgery and 1 year after surgery and compared the scores of the two groups.Results No conversion to open procedure was necessary in either group. The mean TD operative time was 89.2 minutes with a mean intraoperative blood loss of 16.5 mL. Mean MED operative time was 92.0 minutes with a mean blood loss of 19.3 mL. There were two dural tears in the MED group, and one tear was combined with a fracture of the inferior articular process. No dural tears occurred in the TD group. No patients in either group had experienced re-recurrence of lumbar disc herniation at the time of the last follow-up. The JOA score improved significantly after surgery in both groups (p < 0.001).Conclusion TD is a safe and effective surgical approach for the treatment of recurrent lumbar disc herniation. Operative time, intraoperative blood loss, and clinical results compare favorably with MED.
Keywords: recurrent disc herniation; revision surgery; microendoscopic discectomy; lumbar spine; minimally invasive spine surgery